PENGARUH LINGKUNGAN KEJA DAN KESELAMATAN & KESEHATAN KERJA KARYAWAN TERHADAP KEPUASAN KERJA PADA PT. PRIATAMA RIAU KEBUN PULAU RUPAT - Desi Ridawan; Marzolina '; Rio Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was conducted at PT . Priatama Riau Gardens Rupat with the aim of analyzing the influence of the work environment variables and employee safety & health ( k3 ) , the job satisfaction of employees at PT . Riau Priatama Rupat Gardens . Population is staying employees to 116 people. Sampling was conducted using census or sample saturated 54 people made as a sample of respondents , the analysis method used is descriptive quantitative methods , data analysis carried out simultaneously and partial ( multiple linear regression analysis with SPSS version 19.0 ) . From the results of simultaneous testing (Test F), shows that all the independent variables studied had a significant effect on employee job satisfaction variables . Partial regression test (t test ) showed that the variables lingkungankerja (X1)and employee safety & health ( X2) is more significant effect on job satisfaction of employees(Y) at PT. Priatama RiauKebun Rupat. The magnitude of the effect caused by these three variables together against the dependent variable of this means that the variable work environment and occupational health & safety of employees (k3), jointly influencing employee satisfaction with variable percentage of. While , affected by other factors that did not participate in this study. Thus, it can be concluded that the work environment variables and employee safety & health ( k3 ) simultaneously and partially positive and significant effect on job satisfaction of employees at PT. Priatama RiauKebun Rupat . In addition, variable employee safety and health is also a variable that has more influence on employee job satisfaction when compared with variable work environment.Keywords: Work Environment, Safety & Health and employee job satisfaction of employ